2016
DOI: 10.20892/j.issn.2095-3941.2016.0068
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances of sonodynamic therapy in cancer treatment

Abstract: Sonodynamic therapy (SDT) is an emerging approach that involves a combination of low-intensity ultrasound and specialized chemical agents known as sonosensitizers. Ultrasound can penetrate deeply into tissues and can be focused into a small region of a tumor to activate a sonosensitizer which offers the possibility of non-invasively eradicating solid tumors in a site-directed manner. In this article, we critically reviewed the currently accepted mechanisms of sonodynamic action and summarized the classificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
161
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(166 citation statements)
references
References 83 publications
4
161
1
Order By: Relevance
“…The result is a mechanical damage and a consequent induction of cell death by the so called "mechanical pathway" from refs. [88,105], as also depicted in Fig. 3.…”
Section: G Canavese Et Alsupporting
confidence: 57%
“…The result is a mechanical damage and a consequent induction of cell death by the so called "mechanical pathway" from refs. [88,105], as also depicted in Fig. 3.…”
Section: G Canavese Et Alsupporting
confidence: 57%
“…Previous studies have reported that different ultrasonic intensities combined with diverse sound-sensitive agents produce distinct biological effects on specialized cells and tissues [26][27][28]. In this study, we demonstrated that when DVDMS was used in conjunction with ultrasound (diameter: 3.5 cm; resonance frequency: 0.5 MHz; duty factor: 10%; repetition frequency: 100 Hz) on the SCLC H446 cell line, apoptosis was observed.…”
Section: Discussionsupporting
confidence: 51%
“…It uses a combination of low-intensity ultrasound and specialised chemical agents termed sonosensitizers, which are drugs that can be activated by ultrasound. Ultrasound is able to penetrate deeply into tissues and can be focused on a small region of tumor where it activates the sonosensitizer, creating a cascade of endogenous cytotoxic agents [4]. The advantage of ultrasound is that it penetrates more deeply than light, and therefore it is likely to be more effective for the treatment of deeper tumours than PDT [4].…”
mentioning
confidence: 99%
“…SDT is understood to produce cavitation around the surface of cancer cells, with the energy released following the collapse of the cavitating bubbles creating sonoluminescent light in the cancer cells [4]. The sonosensitizer is activated to an excited state from its ground state, and upon return to its ground state, released energy is transferred to the circumambient oxygen.…”
mentioning
confidence: 99%
See 1 more Smart Citation